Host selection, oviposition behaviour and leaf traits in a specialist willow sawfly on species of Salix (Salicaceae) - Braccini, Celina Laura; Vega, Andrea Susana; Chludil, Hugo Daniel; Leicach, Silvia Rosa; Fernandez, Patricia (Wiley, 2019)
Plant genotype influences plant–herbivore interactions by affecting insect attraction, acceptance and development. Here we linked oviposition behaviour of the specialist willow sawfly Nematus oligospilus Förster (Hymenoptera: Tenthredinidae) with leaf traits on different Salix L. (Salicaceae) genotypes. This was done as a first step to find oviposition cues that guide females to their host plants. By means of choice and no‐choice bioassays we analysed host selection according to willow genotype and leaf surface. We also studied larval performance, adult fecundity and effect of experience on host selection. Nematus oligospilus prefers to oviposit on S. nigra. The least preferred genotype, S. viminalis, showed better larval performance and highest adult fecundity. Host preference was not modified by larval feeding experience. By means of light and scanning electron microscopy we described ovipositor and leaf micromorphology. The egg is laid inside the epidermis or between the epidermis and adjacent chlorenchyma, showing a tight association with the leaf. Leaf toughness was lowest for S. nigra and higher for S. viminalis and S. babylonica. Total nitrogen and protein content were higher on S. viminalis and S. babylonica. Total phenolics and phenolic glycosides were the highest and more diverse on S. nigra. Salicin content levels correlate with oviposition preference, suggesting the role of salicylates as oviposition stimulants. Results suggest that oviposition preference on S. nigra may be related to lower leaf toughness and ease of injection of female saw‐like ovipositor, and motivated by the presence of phenolic glycosides. Nitrogen levels may explain better larval performance and adult fecundity in S. viminalis. Thus, a balance among the different leaf traits determines the outcomes observed in this study.